Disability Practice Safeguarding Quality Service Delivery - Bigby, Christine; Hough, Alan (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2024)
This open access book critically engages with the social, political and ethical implications of support for people with disability to be fully included in society. The authors examine contemporary issues of quality and safeguarding in disability services, translating research and practice wisdom into foundational knowledge. Written by leading researchers, the book provides a comprehensive overview of knowledge and practice necessary to prepare readers to deliver enabling support. .